Pengembangan Usaha Bunga Plastik Tiruan: Analisis Pemasaran, Produksi, dan Keuangan - Miftahul Hariz; Mahindah Mahindah; Jasmine Damayanti; Muhammad Yasin (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the factors influencing consumer purchasing decisions for artificial flower products, marketing strategies used, and challenges in production and distribution. A descriptive qualitative approach was applied through a case study on the Fake Flower Plastic business. Data were collected via interviews, observations, documentation, and questionnaires. The results indicate that product quality, aesthetics, pricing, and social media influence significantly affect consumer decisions. Digital marketing via social media and influencer collaboration proved effective in reaching target consumers. Production challenges include raw material efficiency and sustainability, while distribution is hindered by logistics and packaging issues. The study recommends improving product quality, design innovation, and strengthening marketing and distribution strategies to support sustainable business growth.